ANALISIS SWOT TERHADAP STRATEGI PENGEMBANGAN USAHA OTAK -OTAK BANDENG BAKAR HJ LAILA - Sabrina Nurhaliza; Vembri Aulia Rahmi; Aries Kurniawan (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2025)
Traditional culinary businesses have significant potential in the MSME sector, one of which is Hj. Laila's Grilled Milkfish Otak-Otak in Gresik. This study aims to analyze business development strategies using a qualitative approach with a case study method. Data collection techniques included in-depth interviews, observation, and documentation, with informants from the owner, employees, and customers. A SWOT analysis was used to identify the business's strengths, weaknesses, opportunities, and threats. Results indicate that the main strengths lie in product quality and customer loyalty, while weaknesses include limited human resources and seasonal raw materials. Opportunities include the increasing demand for regional souvenirs and the potential for digital marketing, while threats stem from competition from similar businesses. The implemented development strategies include packaging innovation, product diversification, improved customer service, and market expansion. These findings are expected to serve as a strategic reference for culinary MSMEs in developing sustainable development strategies.